2016
DOI: 10.4028/www.scientific.net/amm.818.151
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Assessment of Hybrid Renewable Energy for a Remote Area Electrification in Iran

Abstract: The utilization of renewable resources is growing, in part due to the environmental impacts caused by fossil fuels. The largest sources of renewable energy are wind and solar and many predict that these energy sources will be increasingly used for distributed generation. In this paper, the feasibility is examined of a grid-independent system applied for a remote area electrification in Binalood, Iran. Traditional power systems for remote or rural areas are based on fossil fuels. After addition of renewable ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Their results yielded an NPC of USD 3,569,094 and an LCOE of USD 0.04449/kWh. Other related works have been performed on hybrid systems, as found in [27][28][29][30][31][32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results yielded an NPC of USD 3,569,094 and an LCOE of USD 0.04449/kWh. Other related works have been performed on hybrid systems, as found in [27][28][29][30][31][32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Khavari et al assessed the viability of a hybrid renewable energy systems for the electrification of remote area in Binalood, Iran. They used HOMER to assess the techno-economic benefits of using the system and their results show that the wind-diesel-battery storage hybrid system was the most efficient [24]. Rice et al…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, one study examined the feasibility of using solar and biomass energies in providing electricity for a farming field in Kerman and it was suggested that the utilization of a combinational system of biogas and solar energies is more cost-effective than single energy systems in this region (Heydari and Askarzadeh 2016). In addition, in a study by Khavari et al (2016) the combinational energy systems for an isolated region in Iran were evaluated. This study revealed that the combinational diesel-wind system is the most efficient system for some of the isolated regions.…”
Section: Introductionmentioning
confidence: 99%